Fla. Act of Aug. 6, 1888, ch. 1637, subch. 7, § 10, as codified in Fla. Rev. Stat., tit. 2, pt. 5 (1892) - (:unkn) unknown (My University, 1888)
Prohibited the concealed carrying of slungshot, metallic knuckles, billies, firearms, or other dangerous weapons if arrested for committing a criminal offense or disturbance of the peace. Punishable by imprisonment up to 1 year and a fine up to $50.
Keywords: CARRY - INTENT TO COMMIT CRIME